Šport kot gospodarski in družbeni fenomen v kontekstu trga dela - Andolšek, Jure (Šport (Ljubljana), 2025)
This article examines the intersection between sport and the labor market through a bibliometric analysis of 289 scientific articles published in journals indexed in the Social Sciences Ci-tation Index (SSCI). Using co-word analysis, eight thematic clus-ters were identified, reflecting the intellectual structure of this research field. The clusters highlight three broader themes: the economics of professional sport (wage structures, competitive balance, discrimination), sport as a generator of human capital and employability (education, dual careers, mobility), and sport as a source of social capital and inclusion (health, youth participation, inequality). The findings demonstrate that sport represents a unique laboratory for studying economic and social processes, while simultaneously raising important practi-cal issues for sport organizations, educational institutions, and policymakers. This study contributes to a deeper understanding of the development of research in this area and identifies future opportunities related to digitalization, athlete migration, and the sustainability of the sport labor market.
Keywords: raziskave; razvoj; research; sports; sports management; šport; športni management